Design Analysis and Verification of PMSM Motor For Dishwasher Machine - Akyun, Yakup; Nory, Hayatullah; Talas, Mohamad Zouhair; Kurum, Hasan (Ieee, 2019)
In this paper an interior permanent magnet (IPM) synchronous motor (PMSM) is analytically designed and analyzed by Ansys Maxwell 2D software, and fabricated in Bader Motor Technology Company. Currently, single phase induction motors (IM) are used in dishwasher machine. According to customer requirements; due to controlling of speed, lower price and higher efficiency the PMSM motor are preferred instead of single phase IM. In respect to customer requirement the motor is designed, with 3400 rpm, 0.2 Nm and 0.5 Arms. The designed motor is capable to operate in (2000-3800) rpm range of speed without applying field weakening method. The designed motor is lighter 0.50 kg lower than the IM motor and thanks to efficiency the new motor efficiency is 12 percent higher than the old one. As experiments, noise, heating up and vibration issues of new designed motor are less than the IM.
4th International Conference on Power Electronics and their Applications (ICPEA) -- SEP 25-27, 2019 -- Elazig, TURKEY
Keywords: Permanent Magnet Synchronous Motor (PMSM); Ansys Maxwell 2D; Finite Element Method (FEM); Interior Permanent Magnet (IPM)